The Role of Transformational Leadership on Employee’s Innovative Performance in Colleges in Punjab, Pakistan - Shajar Abbas; Fayiza Parveen; Muhammad Sarwar; Muhammad Arif (Journal of Management Practices, Humanities and Social Sciences, 2024)
The study provides insights into a valuable dynamic of the role of transformational leadership on employees' innovative performance in colleges in Punjab, Pakistan. By applying quantitative data, the study emphasizes how transformational leadership influences innovative performance in educational settings. By applying the qualitative method, the study fills the critical gap in understanding how leadership and employee performance are connected. Using the hierarchical regression technique, the paper examines the role of transformational leadership in employees' innovative performance at the college level in Punjab, Pakistan. Data was gathered through a standard questionnaire from the faculty and administrative staff of public (N = 93) and private colleges (N = 107), and the data was analyzed using a quantitative approach. The survey items comprised in the survey were associated with transformational leadership, innovative performance, organizational support for innovation, job satisfaction and work environment. Results are based on self-administered questionnaires and were analyzed by correlation and regression methods, which reveals a significant positive relationship between transformational leadership and employees' innovative performance. The outcomes highlight the significance of visionary leadership in promoting a creative and innovative setting at educational institutes. The findings are further discussed in the context of theory and practice, which have implications for leadership development programs within higher education.